2018
DOI: 10.3892/or.2018.6627
|View full text |Cite
|
Sign up to set email alerts
|

Association between Tim‑3 and Gal‑9 expression and gastric cancer prognosis

Abstract: The T‑cell immunoglobulin and mucin domain‑containing protein 3 (Tim‑3)/galectin 9 (Gal‑9) pathway, which serves a pivotal role in immune regulation, is similar to the programmed death (PD)‑1/PD‑ligand 1 pathway. Recent evidence has suggested that Tim‑3 is differentially regulated in a variety of tumors and is a potential therapeutic target. The aim of the present study was to evaluate Tim‑3 and Gal‑9 expression and cluster of differentiation (CD)3+, CD8+ and forkhead box (FOX)p3+ T cell tumor‑infiltration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 44 publications
6
44
0
1
Order By: Relevance
“…Interestingly, subgroup analysis showed that TIM-3 overexpression on tumor cells was associated with poor OS, but the association between TIM-3 expression on TILs and OS didn't reach a statistical significance. TIM-3 was mainly expressed on immune cells with lower expression in tumor cells (9,42). It seems that the expression of TIM-3 on tumor cells has greater prognosis value, but the exact mechanism needs further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, subgroup analysis showed that TIM-3 overexpression on tumor cells was associated with poor OS, but the association between TIM-3 expression on TILs and OS didn't reach a statistical significance. TIM-3 was mainly expressed on immune cells with lower expression in tumor cells (9,42). It seems that the expression of TIM-3 on tumor cells has greater prognosis value, but the exact mechanism needs further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…The M subtype had high expression of TGF-β1, and immune checkpoint TIM-3, its ligand galectin-9, and another immune checkpoint VISTA, high proportion of monocytes, increased proportion of M2 macrophage, and enriched abundance of fibroblast in the TME, thus uncovering novel targets for immunotherapy. Although several studies have demonstrated that TIM-3, its ligand galectin-9 and VISTA are dysregulated in GAC tumour tissues and pointed their potential clinical implication,52–56 there are some limitations to these studies due to the study design and was limited to primary tumour tissues and PC cells were not included. However, our discovery on TIM-3/galectin-9 and other immune suppression molecules-VISTA and TGF-β1 were derived from a comprehensive profiling of patients’ PC samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of lactose, Treg cells lose their ability to inhibit the secretion of IFN-γ and IL-17 (16.4 vs. 3.99 ng/ml, n=20, p<0.0001 and 0.74 vs. 0.64 ng/ml, n=15, p=0.005, respectively) [10]. Thus, there is an increase in cellular pro-inflammatory processes, as well as the induction of autoimmune diseases and delayed hypersensitivity reactions that support chronic inflammation [24] and tumor processes [25,26].…”
Section: Resultsmentioning
confidence: 99%